2018
DOI: 10.5603/fm.a2018.0006
|View full text |Cite
|
Sign up to set email alerts
|

Tendon — function-related structure, simple healing process and mysterious ageing

Abstract: Tendons are connective tissue structures of paramount importance to human ability of locomotion. The understanding of their physiology and pathology is gaining importance as advances in regenerative medicine are being made today. So far, very few studies were conducted to extend the knowledge about pathology, healing response and management of tendon lesions.In this paper we summarize actual knowledge on structure, process of healing and ageing of the tendons. The structure of tendon is optimized for the best … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(47 citation statements)
references
References 51 publications
0
44
0
3
Order By: Relevance
“…Tendon injuries are very common and their natural repair process is extremely slow, complex, and inefficient due to their intrinsic hypocellularity and hypovascularity, representing a clinical challenge to orthopedists mainly because these injuries often respond poorly to treatment [ 1 ]. As reviewed by Zabrzyński et al [ 2 ], the occurrence of tendon injuries is associated with sports, aging, tendinophaties, hypothyroidism, hypertension, diabetes mellitus, arthropathies, corticosteroids, vitamin C deficiency, and others. Collagen fibers are the main component of the abundant extracellular matrix (ECM) of tendons, and with the proteoglycans (PG), the collagen fibers form a highly organized supramolecular structure, able to attend to the biomechanical demands on the tissue [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Tendon injuries are very common and their natural repair process is extremely slow, complex, and inefficient due to their intrinsic hypocellularity and hypovascularity, representing a clinical challenge to orthopedists mainly because these injuries often respond poorly to treatment [ 1 ]. As reviewed by Zabrzyński et al [ 2 ], the occurrence of tendon injuries is associated with sports, aging, tendinophaties, hypothyroidism, hypertension, diabetes mellitus, arthropathies, corticosteroids, vitamin C deficiency, and others. Collagen fibers are the main component of the abundant extracellular matrix (ECM) of tendons, and with the proteoglycans (PG), the collagen fibers form a highly organized supramolecular structure, able to attend to the biomechanical demands on the tissue [ 3 , 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…The inflammatory process lasts about 7 days, with the formation of hematoma in the region of the lesion during the acute phase. Inflammatory cells (neutrophils, macrophages and platelets) then begin to release cytokines and growth factors that will stimulate the proliferation of cells and substances in the next step 9,28 . In this study, it was observed that the acute inflammatory process in the LED group occurred more pronouncedly than in the ML group; however, there was a gradual decrease in the amount of inflammatory cells in both groups.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Patellar tendon was used in this study as they are often selected as a graft clinically. Its cellular properties vary depending on the mechanical force that they encounter [32,33]. Tenocytes play an important role in the synthesis of collagen and proteoglycans and thus maintenance of the surrounding extracellular matrix [34], Among tenocytes are also multipotent precursor cells to aid remodeling and adaptation to different surroundings [35].…”
Section: Discussionmentioning
confidence: 99%